2019
DOI: 10.30526/32.1.1983
|View full text |Cite
|
Sign up to set email alerts
|

Gallic Acid as Corrosion Inhibitor for Aluminum 6061 in Alkali Solutions

Abstract: The research aims to study the corrosion of aluminum alloy(6061) in 0.6 mol. dm-3 NaCl solution in base medium  was examined with out and with Gallic acid as environmentally – friendly corrosion inhibitor at temperature range (298-313)K. The inhibitive action of gallic acid on corrosion of aluminum alloy(6061)  in KOH solution was examined through electrochemical polarization method using potentiostatic technique and surface analysis by optical microscopy,  Polarization measurements indicate that the examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…K: represents the surface coverage of the inhibitor, while A: represents the surface coverage of the outer layers of the carbon steel specimens. The time spent underwater is determined by the number of days measured [15,16].…”
Section: Weight Loss Measurementsmentioning
confidence: 99%
“…K: represents the surface coverage of the inhibitor, while A: represents the surface coverage of the outer layers of the carbon steel specimens. The time spent underwater is determined by the number of days measured [15,16].…”
Section: Weight Loss Measurementsmentioning
confidence: 99%
“…Gallic acid application as a corrosion inhibitor for Al and other metals had also been explored. Ali et al reported that it can function as a mixed type inhibitor for AA6061 exposed to alkali solutions [17]. Keny et al.…”
Section: Introductionmentioning
confidence: 99%